Robert Ludlum's The Treadstone rendition [large type] - Hood, Joshua; Ludlum, Robert, 1927-2001 (Hood, Joshua. Treadstone series ;, 2023)
"Adam Hayes promised his wife that he won't put his life on the line any more, and there's nothing that will make him break it. Well, almost nothing. With America withdrawing from Afghanistan and the Taliban closing in, Abdul Nassir reached out to his old friend. The Afghan is the only eyewitness to a massacre committed by a rouge team of CIA contractors. Not only can he identify the butcher who directed the bloodbath, he has photographic proof. He'll only be safe when those pictures are made public. Now, there's just one man he can trust to get him to safety, Adam Hayes"--